Yield estimation model for lithography hotspot distortions. Issue 17 (1st August 2013) - Gómez, S.; Moll, F.
Abstract : A yield formulation model to estimate the amount of lithography distortion expected in a printed layout is proposed. The yield formulation relates the probability of non‐failure of a lithography hotspot with the yield loss. The application of the yield model is demonstrated for three different layout configurations showing that unidimensional designs may improve manufacturing yield.